MINI-REVIEW: APLIKASI SPEKTROFOTOMETRI UV-VIS PADA PENETAPAN PENGARUH MATRIKS TERHADAP PB DENGAN PENGOMPLEKS ALIZARIN SULFONAT - Nurhafida; Bohari Yusuf; Alimuddin (PROSIDING SEMINAR KIMIA, 2025)
Heavy metal contamination, particularly lead (Pb), is a serious environmental issue due to its toxic nature and ability to accumulate in the food chain. Common analytical methods such as AAS and ICP-OES offer high accuracy but require expensive instruments and complex procedures. As a simpler and more economical alternative, UV-Visible spectrophotometry utilizes the formation of coordination complexes between Pb²⁺ ions and complexing reagents such as alizarin sulfonate. This mini review discusses the interaction between Pb and alizarin sulfonate, the working principle of UV-Vis spectrophotometry, and the influence of sample matrices on complex stability. The review indicates that this method provides valid, rapid, and efficient results, and can be effectively applied to environmental samples with complex matrices, provided appropriate sample preparation and method validation are conducted. Keywords: Lead (Pb), UV-Vis Spectrophotometry, Alizarin Sulfonate, Complex Formation